Pemberdayaan Jemaat Gereja HKBP Sipange Dalam Membangun Eco-Tourism Wisata Pantai Pandan Sibolga - Susilawati Panjaitan (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This research was conducted at the HKBP Sipange church in building Eco-Tourism for Pandan beach tourism in Sibolga, Pandan District, Central Tapanul, North Sumatra. Knowing the factors that limit the suitability index value of the HKBP Sipange church in building Eco-Tourism for Pandan beach tourism in Sibolga, factors which supports the profitability of beach tourism and to find out the Tourist Suitability Index (IKW). This research was conducted for 1 month, namely. From the beginning of March -April to the beginning of  Oktober 2023. The method used in this research is a descriptive, quantitative method. Determining the research location point is based on the regional representation of the object by considering the area of tourist activities such as point 1, water point, point 2, namely. Swimming activities and point 3 are often carried out. Boat operations that transport passengers around the island. The parameters measured in the Suitability Index for the HKBP Sipange church in building Eco-Tourism for Sibolga Pandan beach tourism, the beach tourism category are depth, type of beach, width of the beach, groundwater material, slope of the beach, speed. Currents, clarity, coastal land cover, biota threats and fresh water availability. Based on observations, the potential of Pandan Beach is that it has white sand and the waves are not too big. The results of the investigation show that the tourism suitability index of the three stations is that the value for station 1 is 2.695, while stations II and III have the same value, namely 2.795. This shows that Pandan Beach is very suitable (SI) for the category with a tourism suitability index value of 2.5. This shows that Pandan Beach, Central Tapanul, North Sumatra has a very good opportunity to become a destination for recreational beach tourism activities.